Knowledge Tourism - Gorry, G. Anthony (Journal of Knowledge Management Practice, 2012)
In permeating our lives, digital technology has changed not only how we know, but also what we deem worth knowing. We have become tourists in the burgeoning electronic realm of knowledge, returning from our forays with snippets of knowledge as souvenirs of our travels. Within businesses, this way of knowing about the world by cobbling together diverse pieces of understanding threatens to foster organizational learning that is increasingly broad but increasingly shallow. Businesses should counter this threat by retaining some traditional guideposts to learning in their knowledge management systems as these systems extend into social networks on the Internet.